Implementation of Green Disaster Management Policy by BPBD Surabaya City: A Sustainable Approach to Disaster Management - Muhammad Amrul; Ika Devy Pramudiana; Sapto Pramono (International Journal of Humanities and Social Sciences Reviews, 2025)
This study examines the implementation of Green Disaster Management (GDM) policies by the Surabaya City Disaster Management Agency (BPBD) as a means to enhance disaster resilience through environmental sustainability. The research analyzes the integration of GDM principles across all phases of the disaster cycle pre-disaster, during response, and post-disaster recovery. Data was collected through in-depth interviews with key informants, participant observation, and document analysis at BPBD and pilot project sites, including mangrove conservation areas, green emergency posts, and eco-friendly reconstruction sites. The findings indicate that Surabaya has demonstrated significant commitment to embedding sustainability into disaster management through community education, environmentally friendly logistics, and eco-based mitigation measures. Nonetheless, challenges persist, such as limited funding, resistance from developers, logistical constraints, and societal perceptions favoring immediate response over environmental considerations. During disaster response, innovations such as solar-powered emergency equipment and waste segregation practices are being adopted, but their widespread application remains hampered by resource limitations. Post-disaster, efforts in eco-friendly reconstruction and reforestation programs have shown promising results but require enhanced public awareness and long-term maintenance. The success of GDM implementation depends on effective inter-agency coordination, political commitment, and community engagement. Despite progress, hurdles related to budget constraints, social resistance, and knowledge gaps fully hinder the adoption of green approaches. This study highlights the importance of strategic collaboration, policy support, and community participation to mainstream sustainability in disaster management continuously. Strengthening these aspects will not only improve Surabaya's disaster resilience but also contribute to sustainable urban development aligned with global frameworks such as the Sendai Framework for Disaster Risk Reduction.